Polymer-based film, production method therefor, and use thereof
Patent Information
- Application Number
- JP2024213076
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025032237000003 
Figure 2025032237000004 
Figure 2025032237000005
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of membranes, their preparation and use. In particular, the present invention relates to a polymer-based membrane having a loofah sponge-like structure, its preparation and use, as well as a functional material comprising the membrane, in particular a filtration or separation membrane. [Background technology]
[0002] Nanofibers found in nature, such as spider silk and silkworm silk, have attracted widespread attention due to their excellent properties. However, the industrialization of such nanofibers has been limited due to the lack of natural resources. Researchers have been exploring for many years to artificially produce nanofibers. Among them, electrospinning technology has become one of the main methods for efficiently producing nanofiber materials. This is because it has the advantages of simple production equipment, low spinning cost, the ability to spin a wide variety of materials, and the controllability of the production process.
[0003] Electrospinning is a method that is carried out under a strong electric field as follows. First, droplets formed from a polymer solution or melt are transformed from a spherical to a conical shape at the tip of a needle. Then, the tip of the cone is stretched to obtain a fiber filament, which is jet-spun. Then, in a receiving device, the spun filament is solidified. In this way, polymer filaments with a diameter of several nm to several μm can be produced. Fibers obtained by electrospinning have a large specific surface area, a high porosity, and special physical and chemical properties. Therefore, in recent years, fibers obtained by electrospinning have been widely used in the fields of environmental protection, health, energy, etc. (materials for high-efficiency filters and separation membranes in environmental governance, membrane materials for energy storage and conversion in energy devices, tissue culture and wound dressings in the medical field, etc.). Research has provided nanofibers with various morphologies and functions. The variations are mainly achieved by changing the material (CN109713203A), by using composites of multiple materials (J. Power Sources, 2014, 261, pages 1-6), and by controlling the morphology (Adv. Funct. Mater. 2018, 28, 1705051).
[0004] However, the production of nanofiber membranes by electrospinning technology still faces several problems to be solved. Various industrial-scale electrospinning machines equipped with various kinds of spinning and recovery accessories have been devised. However, in many cases, the yield is too low. The spinning efficiency at the current state of the art is low, at most a few grams per hour per needle. The yield of one machine is limited to a few tens of kg per day. Therefore, most of the final products are only used at the laboratory stage. In addition, high voltage electricity exposes workers to operational hazards. In addition, in solution electrospinning, the solvent usually accounts for 70-90% by weight of the solution. If the solvent evaporates into the environment, it will cause environmental burden, safety hazards, and chemical waste. In addition, the use of flammable organic solvents will cause fire hazards and environmental risks because the organic solvents will easily volatilize and generate large amounts of flammable gases. Therefore, it is particularly important to design nanofiber separation membranes that are spun with high yields using environmentally friendly techniques. In addition, the nanofiber membrane produced by electrospinning takes the form of a nonwoven fabric. Its microstructure is shown in the electron microscope photograph in Figure 9 (quoted from J. Mater. Chem. B 2014, 2, 181-190). In general, the fibers in the nanofiber membrane are layered and overlapped, and the fibers in different layers are not firmly fixed to each other. Therefore, the structural stability is insufficient for application in situations that need to withstand large impact forces (such as liquid filtration).
[0005] On the other hand, the demand for water resources is increasing in modern society. However, population growth and economic development since the Industrial Revolution have inevitably generated large amounts of wastewater (especially oily wastewater). In order to recycle this wastewater, it is necessary to treat it appropriately. Membrane water treatment technology is widely used in water treatment processes (especially separation of oil-water mixtures). This is because the process of this technology is simple, low-cost, energy-saving, and highly efficient.
[0006] The most difficult part to separate from oily wastewater is emulsified oil. The particle size of the oil droplets is mainly 0.1 to 2 μm, and is usually less than 10 μm. The oil droplets are stably dispersed in water in the form of oil-in-water. In order to treat such oily wastewater, research on superhydrophilic and superoleophobic separation membrane materials has attracted much attention.
[0007] Microfiltration membranes have a place in the field of membrane separation due to their small pores and relatively low cost of use. Microfiltration membranes primarily rely on mechanical sieving, which allows the passage of macromolecules and soluble solids, but not larger substances such as suspended solids, bacteria, and high molecular weight colloids.
[0008] Liquid separation membranes often suffer from irreversible membrane fouling during the separation process. Therefore, it is necessary to develop a membrane with a suitable surface microstructure that ensures permeability. This will reduce the adhesion of foulants to the membrane surface and extend its service life. For example, in an oil-water separation process, three phases, solid, oil, and water, are usually in contact. To facilitate the movement of oil droplets without sticking to the surface, it is ideal to construct a rough micro-nanostructured surface with discontinuous three-phase contact lines. A recent report on the construction of micro-nanostructured separation membranes is the preparation of PAA-g-PVDF membranes by salt-induced phase separation (Angew. Chem. Int. Ed. 2014, 53, 856-860). PAA-g-PVDF membranes are used for the effective separation of oil-water emulsions. However, PAA-g-PVDF membranes have high raw material costs and generate large amounts of wastewater with high salinity. Separately, for example, CN109316981A reports that highly branched polyether is grafted onto the hydrophilically modified membrane surface. The numerous long branches can penetrate deeply into the oil-water interface of the emulsion, destroying the strength of the emulsion interface membrane. This achieves the demulsification separation action. Also, in CN109046034A, polyvinylidene fluoride is modified with polydopamine / silica powder to obtain a hydrophilic / oleophobic vinylidene fluoride separation membrane. Adv. Funct. Mater 2018, 28, 1705051 reports that a lotus leaf-like structured surface was constructed by a combination of electrospinning and electrostatic spraying. The prepared separation membrane had a high porosity and a mastoid structure similar to the lotus leaf surface was distributed on the membrane surface, which separated O / W (oil-in-water) emulsions with high efficiency and had antifouling properties. Other methods that have been reported include an organic-inorganic hybrid metal mesh membrane (CN110280222A) and chemical grafting onto the membrane surface (CN109499393A).
[0009] However, most of the existing methods for producing separation membranes having a micro-nano composite structure have the disadvantages of high material and production costs, complicated production operations, inability to produce continuously, and difficulty in industrialization.Furthermore, they also have the disadvantages of not being able to maintain the rough micro-nano structure of the membrane surface for a long period of time, and a narrow range of membrane separation applications.
[0010] Furthermore, in the conventional vapor-induced phase separation (VIPS) method for membrane production, a non-solvent is introduced from the gas phase into the polymer solution. In this case, the precipitation is very slow. Because the introduction of the non-solvent is slow, there is no concentration gradient of the membrane-forming liquid in the thickness direction of the membrane. The membrane-forming liquid precipitates almost simultaneously in the thickness direction of the entire film. However, the membrane-forming process of the VIPS method is very slow, and the membrane-forming time usually takes several hours, making it inefficient and difficult to achieve industrial continuous production. In addition, when a porous material such as a non-woven fabric is used as the support layer, it is not suitable for the production of practical separation or filtration membranes (especially porous membranes).
[0011] Therefore, there is a need for improved membranes that are suitable for separation or filtration, have improved overall performance, and can be efficiently manufactured using inexpensive raw materials, at low cost, and with simple processes. Summary of the Invention
[0012] In view of the above problems in the prior art, the object of the present invention is to provide a membrane having a highly penetrating pore (void) structure and a three-dimensional fiber network structure, which has excellent separation or filtration effect, is particularly suitable for use as a microfiltration membrane for oil-water separation, and has high structural stability.
[0013] In particular, it is also an object of the present invention to provide a membrane having a special surface microstructure, which has special wettability and therefore improved anti-fouling properties.
[0014] Another object of the present invention is to provide a method for producing the membrane, which is efficient, has low cost and is a simple manufacturing process. Moreover, the membrane can be made from commodity polymers, so the raw material costs are low.
[0015] According to the present invention, it has been unexpectedly discovered that a method combining atomization pretreatment and non-solvent induced phase separation (NIPS, also known as non-solvent phase inversion) can efficiently produce organic polymer-based membranes with a loofah sponge-like structure. The loofah sponge-like structure includes a fibrous framework structure formed by three-dimensionally interwoven and interconnected polymer fibers, and a three-dimensionally interpenetrating network of pores distributed in the fibrous framework. In particular, when two or more polymers are used, a micro-nano composite structure with nanoscale protrusions on the fibrous framework is obtained. This achieves the object of the present invention.
[0016] The pores on the surface of the membrane according to the present invention and the pores of the open structure penetrating the internal structure of the fiber skeleton constitute a gap. This gap is similar to the gap between overlapping fibers in a nanofiber membrane structure produced by electrospinning. This gap allows the membrane to exhibit effects in separation, filtration, adsorption, etc. equal to or greater than those of a nanofiber membrane structure. On the other hand, the membrane of the present invention is different from the nanofiber membrane obtained by electrospinning. That is, the polymer of the membrane of the present invention exhibits a three-dimensional fiber network structure, and the polymer fibers are directly interconnected in three dimensions. That is, they are radially connected in three-dimensional space, not overlappingly connected. In the membrane of the present invention, the polymer fibers are firmly connected, so that the structural stability and strength of the membrane are improved.
[0017] 〔film〕 Thus, in a first aspect, the present invention provides a polymer-based membrane having a loofah sponge-like structure. The loofah sponge-like structure has a fibrous skeletal structure and a network-like pore structure. The fibrous skeletal structure is formed by three-dimensionally interwoven and interconnected polymer fibers. The network-like pore structure is three-dimensionally interpenetrating and distributed in the fibrous skeletal structure. The polymer is an organic polymer. The fibrous skeletal structure is integrally formed from the polymer. The volume porosity of the membrane is 50% to 95%. The membrane has a highly penetrating bidirectionally continuous network-like pore structure.
[0018] In this specification, the term "membrane" refers to a functional material having a film-like structure (such as a separation membrane or a filtration membrane).
[0019] In the present specification, the term "loofah sponge-like structure" refers to a structure similar to the loofah sponge structure. The loofah sponge-like structure has a fibrous skeleton structure formed by three-dimensionally interwoven and interconnected polymer fibers, and a three-dimensionally interpenetrating network-like pore structure distributed in the fibrous skeleton structure (see, for example, Figures 1 to 6). The structure of the loofah sponge is shown in Figure 10. This figure is a photograph of a loofah sponge. It can be seen that the internal fibrous layer of the loofah sponge structure is a three-dimensional cubic structure, not a laminated structure. That is, the connection points of the same fibrous layer and various longitudinal fibers are not in the same plane. The polymer fibers of the membrane of the present invention interpenetrate in three dimensions, forming a three-dimensional network-like structure that is strongly interconnected. This structure is similar to the loofah sponge structure shown in Figure 10 (i.e., similar to the loofah sponge-like structure defined above). In this three-dimensional network-like structure, the internal fibrous layer also has a three-dimensional cubic structure, not a laminated structure. That is, the connection points between the same fiber layer and various longitudinal fibers are not in the same plane. At this time, the pores between the fibers constitute the through-pore structure of the polymer membrane described above. The membrane according to the present invention having such a loofah sponge-like structure has a highly through-pore network structure, a high porosity and specific surface area, and excellent structural stability.
[0020] As used herein, "three-dimensionally interwoven" means that the polymer fibers are distributed in a staggered manner with different thicknesses within and between the fiber layers. The polymer fibers are not parallel to each other. Also, the fibers (also called longitudinal fibers) connecting the various fiber layers are not parallel to each other. The connection points of the same fiber layer with the various longitudinal fibers are not in the same plane. Therefore, the fiber skeleton structure is shapeless and a network-like pore structure is formed between the fibers. The connection points of the fibers that make up each pore are not in the same plane or in the same fiber layer.
[0021] As used herein, "three-dimensionally interconnected" means that the polymer fibers are interconnected toward the surface of the membrane, and are interconnected from the surface of the membrane to the interior of the membrane, or in other words, that the polymer fibers are interconnected radially in three-dimensional space.
[0022] As used herein, "three-dimensionally interpenetrating" means that the pore structure of the membrane penetrates from the surface of the membrane to the interior of the membrane, both vertically and horizontally, and also penetrates within the membrane in a direction parallel to the surface of the membrane.
[0023] In the membranes of the present invention, the fibrous framework is integrally formed from the polymer. The polymer fibers are directly connected throughout. Such membranes are formed from the polymer in one step during the manufacturing process.
[0024] In the fiber skeleton structure of the membrane according to the present invention, the average distance between two adjacent connection points in the thickness direction may be smaller than the average distance between two adjacent connection points in the surface direction.
[0025] In the cross section of the membrane of the present invention, substantially the same type of pores may be distributed in the thickness direction of the membrane. As is well known in the art, the types of pores in the membrane mainly include mesh-like pores, sponge-like pores, finger-like pores, etc. In the cross section of a microfiltration membrane or ultrafiltration membrane obtained by a conventional non-solvent induced phase separation method, different types of pore structures often appear simultaneously. For example, a sponge-like pore structure is present near the surface layer of the membrane, and a large finger-like pore structure is present near the center and bottom of the membrane. In the cross section of the membrane of the present invention, mesh-like pores are distributed in the thickness direction of the membrane, and other types of pores (such as sponge-like pores and / or finger-like pores) are substantially absent. The membrane of the present invention preferably has only mesh-like pores distributed from the surface to the inside. The cross section of the membrane of the present invention is a structure formed by a polymer fiber skeleton structure and pores, and may have a substantially constant shape in the thickness direction of the membrane. In other words, in the cross section of the membrane, a polymer fiber skeleton structure and substantially the same type of pores may be distributed in the thickness direction of the membrane. In other words, the pores distributed throughout the cross section of the membrane are substantially the same type, and the types of pores are not different between the surface layer of the membrane and the bottom layer of the membrane. "Substantially the same type" means that due to the manufacturing method, a small number of different types or imperfect pore structures may inevitably exist in the cross section of the membrane. However, the same type of pores (network pores) are distributed overall in the cross section of the membrane.
[0026] In this specification, the term "microfiltration membrane" generally refers to a filtration membrane having an average pore size of 0.1 to 10 μm, and the term "ultrafiltration membrane" generally refers to a filtration membrane having an average pore size of 10 to 100 nm.
[0027] In the fibrous framework of the membrane of the present invention, the cross-sectional diameter of one polymer fiber between two junctions may be 2 μm or less and may vary randomly. The cross-sectional diameter of the fiber is measured by scanning electron microscopy (SEM).
[0028] In this specification, the term "one polymer fiber" refers to a single fibrous portion present between two connection points in a fibrous skeleton structure. The so-called fibrous portion refers to a portion distributed in a thread-like manner in the membrane skeleton.
[0029] In the fibrous framework of the membrane of the present invention, the length of one polymer fiber between two connecting points can be less than 10 μm when measured by SEM. In the fibrous framework of the SEM photograph shown in FIG. 5, this length is characterized by the linear distance between the start point and the end point of the fibrous part existing between two connecting points. The length of one polymer fiber is significantly shorter than the length (at least cm scale) of one polymer fiber in the nanofiber membrane produced by the electrospinning method. Therefore, the fibrous framework of the present invention is clearly different from the fibrous structure obtained by the electrospinning method.
[0030] The average pore size of the membrane according to the present invention may be 0.01 to 5 μm, preferably 0.1 to 3 μm, and more preferably 10 nm to 3 μm. The average pore size of the membrane is measured by a gas permeation method (for example, using a pore size analyzer).
[0031] The membrane of the present invention has a highly penetrating network pore structure and has a high porosity. The volume porosity of the membrane of the present invention may be 50% to 95%, preferably 65% to 95%, and more preferably 80% to 95%. The volume porosity of the membrane is measured by a gravimetric method.
[0032] In a preferred embodiment, the polymer fibers of the membrane of the present invention have an internal hollow structure, which further increases the porosity and specific surface area, improving the adsorption properties.
[0033] The membrane of the present invention is polymer-based and mainly made of polymer. The polymer is an organic polymer. Examples of organic polymers include, but are not limited to, any common polymer suitable for membrane production, or modified polymers thereof. Preferably, the organic polymer is selected from any polymer suitable for membrane formation by non-solvent induced phase separation method. The polymer may be, for example, one or more selected from the group consisting of polyvinylidene fluoride, polysulfone, polyethersulfone, polyacrylonitrile, polyacrylic acid, polylactic acid, polyamide, chitosan, polyimide, modified cellulose (such as cellulose acetate), polystyrene, polyolefin, polyester, polychlorotrifluoroethylene, polyvinyl chloride, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, modified starch, polyvinylamine hydrochloride, polyethyleneimine, poly-N-isopropylacrylamide, and modified polymers thereof (such as polyvinylidene fluoride modified by grafting with acrylic acid, sulfonated polysulfone, maleic anhydride grafted polysulfone, sulfonated polyethersulfone, and acrylic acid grafted polyacrylonitrile).
[0034] The polymer may be a hydrophilic or oleophilic polymer to produce membranes with different wettability (such as hydrophilic or hydrophobic membranes).
[0035] The hydrophilic polymer can be selected from polymers that have a certain degree of hydrophilicity themselves. Examples of hydrophilic polymers include, but are not limited to, one or more of sulfonated polyethersulfone, polylactic acid, polyester, chitin, crosslinked polyvinyl alcohol, modified cellulose, modified starch, polyethylene glycol, chitosan, polyacrylonitrile, polyvinylamine hydrochloride, polyacrylic acid, polymer hydrogels (such as poly-N-isopropylacrylamide hydrogels), cellulose acetate, polyethyleneimine, polyamides, polyimides, etc. Alternatively, the hydrophilic polymer can be a polymer modified by grafting hydrophilic groups or a block copolymer having hydrophilic groups. Examples include one or more copolymers or branched polymers obtained by grafting hydrophilic moieties (acrylic acid groups, maleic anhydride groups, polyethylene glycol groups, sulfonic acid groups) or polymers obtained by block copolymerization thereof. Specific examples include polyvinylidene fluoride modified by grafting with acrylic acid, sulfonated polysulfone, sulfonated polyethersulfone, maleic anhydride grafted polysulfone, acrylic acid grafted polyacrylonitrile, etc. Preferably, the hydrophilic polymer may be one or more selected from the group consisting of sulfonated polyethersulfone, polyacrylonitrile, polyacrylic acid, polylactic acid, polyamide, chitosan, polyimide, polyester, chitin, cellulose acetate, etc.
[0036] The hydrophobic polymer may be one or more selected from the group consisting of polyvinylidene fluoride, polysulfone, polyethersulfone, polyolefin, polychlorotrifluoroethylene, polyvinyl chloride, polystyrene, and the like.
[0037] The molecular weight of the polymer is not particularly limited, as long as it is suitable for forming a three-dimensional fiber skeletal structure by membrane formation (particularly by non-solvent induced phase separation method).
[0038] In one embodiment, the surface of the membrane of the present invention may have a micro / submicron size recessed structure. The loofah sponge-like structure is distributed on, around, or between the recessed structures. The recessed structure can increase the contact area between the liquid and the loofah sponge-like structure or the mesh-like pore structure. The recessed structure can also further increase the roughness of the membrane surface. Therefore, the separation efficiency or filtration efficiency of the membrane can be further improved.
[0039] The size of the recessed structure measured by SEM may be 0.5 to 10 μm. The size of the recessed structure is characterized by the diameter of the opening of the recess on the membrane surface in the SEM photograph. The size of the recess is significantly larger than the pores of the loofah sponge-like structure or the average pore size of the membrane. Preferably, in this embodiment, the average pore size of the membrane is 10 nm to 3 μm. Preferably, the membrane having the recessed structure is prepared using a hydrophilic polymer as a matrix.
[0040] The film of the present invention may further contain additives that are commonly used in film production. Examples of additives include various inorganic nanoparticles (e.g., nanoscale inorganic fillers such as MnO2, SiO2, ZnO, etc.). The film of the present invention may also contain inorganic salt porogens remaining from the film production process (e.g., LiCl, ZnCl2, MgCl2, LiBr, etc.).
[0041] The membrane may be present on a support layer (eg, a fabric, preferably a nonwoven fabric).
[0042] The membrane of the present invention has a microstructure similar to that of a loofah sponge. In this structure, the three-dimensional network-like through-pore structure is densely distributed, so that the surface roughness (Ra) of the porous membrane is significantly increased. Ra may be 1 to 10 μm, and is measured by a non-contact optical profile analysis method. When the surface roughness increases, the wettability of the membrane surface is improved, and the hydrophilic surface becomes even more hydrophilic, and the hydrophobic surface becomes even more hydrophobic. The increase in wettability is beneficial for improving the selective separation ability of the membrane. Due to the synergistic effect of the pore structure and the surface / interface wettability, the obtained hydrophilic membrane exhibits strong hydrophilicity and strong oleophobicity in water, and has excellent oil-water separation efficiency. In addition, after the membrane surface comes into contact with water, a highly stable hydrated protective layer can be formed on the membrane surface. Therefore, the membrane has the effect of suppressing the adhesion of oil droplets in water, and this effect can be further enhanced if the membrane surface has a recessed structure. In addition, the obtained hydrophobic membrane exhibits strong hydrophobicity and oleophobicity. Due to this special wettability, the membrane of the present invention can be effectively used in the fields of separation, filtration, adsorption, etc. The membrane of the present invention exhibits excellent properties such as high flow rate, high capture rate, self-cleaning property, low adhesion, and high adsorption rate. For example, when the membrane of the present invention is used as a separation membrane, an oil-water separation rate of more than 99% can be achieved for O / W type emulsified oil with an average oil droplet diameter of 300 nm to 3 μm. In addition, since the polymer fibers are three-dimensionally connected to form a strong fiber skeleton structure, the structure and properties of the membrane of the present invention are stable. Therefore, the fiber slip phenomenon that occurs when using an electrospinning membrane does not occur.
[0043] [Membrane having a micro-nano composite network structure] In one embodiment, the membrane may have nanoscale protrusions distributed on the fibrous framework, forming a micro-nano composite network structure, which provides special wettability and improves the antifouling properties of the membrane.
[0044] The protrusions are formed integrally with the fiber skeleton. The size of the protrusions may be 20 to 400 nm when measured by SEM. The protrusions are generally in the form of particles. Therefore, the size of the protrusions represents the average particle size of the particles.
[0045] In this embodiment, the average pore size of the membrane may be from 0.1 to 5 μm.
[0046] The micro-nano composite network structure or micro-nano structure according to the present invention refers to a structure having a micro-scale network skeleton and nano-scale protruding small particles on the skeleton. The presence of such a micro-nano structure gives the membrane a special wettability, namely hydrophilicity in air / superoleophobicity in water, and the adhesion of oil is extremely low. In addition, the sieving channels formed when constructing the rough surface of the membrane give the membrane oil-water separation properties. The micro-nano structure on the surface allows a highly stable hydrated protective layer to be formed on the surface of the membrane after contact with water. The hydrated protective layer inhibits the contact of oil droplets with the membrane, and therefore has the effect of suppressing the adhesion of oil droplets in water. Furthermore, the network skeleton of the membrane is a micro-nano composite structure. Therefore, the three-phase contact line of solid-water-oil becomes discontinuous in water. Therefore, the membrane is superoleophobic in water, and oil does not adhere to the membrane.
[0047] In this embodiment, the membrane typically comprises a mixture of two or more polymers. Useful polymer types are described above. Preferably, the two or more polymers are hydrophilic polymers that are soluble or miscible in the same good solvent.
[0048] Preferably, the first polymer may be one or more of polyvinyl chloride, polysulfone, polyethersulfone, sulfonated polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, acrylonitrile-styrene copolymer (AS resin), and modified polymers thereof, but is not limited thereto. The second polymer may be soluble in a good solvent of the first polymer or miscible with the first polymer. The second polymer may be one or more of chitosan, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, and polyoxyethylene-polyoxypropylene ether block copolymer, but is not limited thereto.
[0049] The weight ratio of the first polymer to the second polymer may be 1:(0.01-5), and is preferably 1:(0.1-3).
[0050] The membrane having a micro-nano composite network structure made by two or more hydrophilic polymers can achieve both superhydrophilicity and superoleophilicity in air.Preferably, the contact angle with water and the contact angle with oil in air are both less than 10°, more preferably less than 5°.The contact angle with oil in water can be more than 135°, preferably more than 150°.
[0051] The membrane having a micro-nano composite network structure made of two or more hydrophobic polymers can achieve superhydrophobicity in air. Preferably, the contact angle with water in air is greater than 130°, more preferably greater than 150°. The contact angle with oil in water can be less than 10°, preferably less than 5°.
[0052] [Manufacturing method] In a second aspect, the present invention provides a method for producing a membrane according to the present invention, comprising subjecting a membrane casting solution containing a polymer to a combination of non-solvent induced phase separation and atomization pretreatment to produce a membrane.
[0053] Specifically, the production method may include the following steps (1) to (3). (1) A step of dissolving a polymer in a solvent to prepare a polymer solution which is a membrane flow solution. (2) A step of applying the polymer solution in a film form and then pretreating it by atomization. The polymer solution is applied, for example, by blade coating. Here, the pretreating step is to retain the polymer solution in a bath of atomized droplets. (3) A step of immersing the product obtained in step (2) in a coagulation bath to obtain a membrane.
[0054] In the above step (1), the concentration of the polymer solution may be 5 to 25% by weight, and preferably 6 to 20% by weight. The prepared polymer solution is used as a membrane casting solution.
[0055] The types of polymers used are as described above.
[0056] The solvent may be selected from good solvents capable of dissolving the polymer, including, but not limited to, one or more of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide, dimethylsulfoxide, tetrahydrofuran, dioxane, acetonitrile (CH3CN), acetone, chloroform, toluene, benzene, hexane, and octane.
[0057] As used herein, the term "good solvent" refers to a solvent that has a high ability to dissolve a polymer solute and has an interaction parameter χ with the polymer solute of less than 0.5.
[0058] As used herein, the term "poor solvent" refers to a solvent that has a low ability to dissolve a polymer solute and has an interaction parameter χ with the polymer solute of 0.5 or more.
[0059] The polymer solution or film casting solution may also contain conventional additives suitable for the production of membranes. Examples of such additives include inorganic salt porogens and / or various inorganic nanoparticles (such as nanoscale inorganic fillers). The content of the additives may be the same as conventional, or may be adjusted according to the actual situation. The additives may be dissolved or dispersed in the polymer solution or film casting solution. Examples of commonly used inorganic salt porogens include LiCl, ZnCl2, MgCl2, LiBr, etc. Examples of inorganic fillers include MnO2, SiO2, ZnO, etc. The polymer solution or film casting solution may also contain a poor solvent for the polymer. Examples of poor solvents include (but are not limited to) water, various small molecule alcohols, etc.
[0060] Preferably, after the polymer solution or membrane casting solution is prepared, it may be degassed.
[0061] In step (2), the polymer solution may be coated uniformly onto a support layer or substrate to form a film.
[0062] The support layer or substrate may be any support layer material or substrate suitable for applying or coating the polymer solution. Examples of support layer materials or substrates include, but are not limited to, porous support materials (such as fabrics, including nonwoven fabrics, woven fabrics, etc.) and smooth substrates (such as glass plates, plastic films, etc.). When a support layer is used, the completed membrane of the present invention is ultimately located on the support layer. In this case, the manufacturing method of the present invention may be a continuous operation (such as a roll-to-roll continuous method). When a substrate is used, the completed membrane of the present invention may ultimately be peeled off from the substrate to form a free-standing membrane.
[0063] The step of applying the film can be carried out by a normal film application method. For example, a casting method in which the film is blade-coated using a doctor blade can be mentioned. Here, the thickness of the film to be applied is not particularly limited. The thickness of the film may be 50 to 500 μm, preferably 75 to 300 μm. Depending on the type of polymer and the thickness of the film to be blade-coated, the thickness of the dry film finally produced may be several μm to several hundred μm, preferably 5 to 60 μm, and more preferably more than 10 μm to 60 μm.
[0064] In step (2), the pre-atomization treatment is a process in which the polymer solution is allowed to stay in the atomized droplet bath for a certain period of time after application or coating, and is brought into contact with the polymer solution. The time for the pre-atomization treatment may be 1 second to 20 minutes, preferably 5 seconds to 3 minutes, more preferably 5 to 60 seconds, and more preferably 5 to 50 seconds.
[0065] In this specification, the method for obtaining the atomized droplet bath is not particularly limited. Various conventional liquid atomization methods may be used, such as pressure atomization, rotating disk atomization, high-pressure airflow atomization, and sonic atomization (particularly ultrasonic atomization). A conventional atomization device can be used to atomize the liquid, and an atomized droplet bath can be obtained. The size (particle size) of the droplets in the droplet bath may be 1 to 50 μm, and more preferably 5 to 18 μm.
[0066] The droplets of the droplet bath contain a poor solvent for the polymer. The poor solvent may be a single component solvent (such as water, e.g., deionized water, ethanol and ethylene glycol). Alternatively, the poor solvent may be a mixture of solvents that includes water (such as a mixture of water and a polar aprotic solvent or other solvents). Alternatively, the poor solvent may be a solvent that includes a salt, an acid, a base, etc.
[0067] The humidity conditions in the atomization pretreatment operation affect the exchange rate between the solvent and the non-solvent, and therefore may affect the microstructure of the film. The humidity of the droplet bath may be a relatively low humidity state of less than 40% or a relatively high humidity state of 40% or more.
[0068] At room temperature (about 25°C), under relatively low humidity conditions of less than 40%, micro / submicron-sized recessed structures can be formed on the surface of a membrane made from a polymer (especially a hydrophilic polymer). Under relatively high humidity conditions of 40% or more, a uniform fiber network structure is formed on the surface of the membrane, and no clear recessed structures are observed.
[0069] In step (3), the coagulation bath used in subjecting the membrane to the NIPS phase inversion process contains a poor solvent for the polymer. The poor solvent may be the same as or different from the solvent contained in the droplets of the droplet bath. The poor solvent may be a one-component solvent (such as water, ethanol, and ethylene glycol). Alternatively, the poor solvent may be a mixed solvent containing water (such as a mixed solvent composed of water and a polar aprotic solvent or another solvent). Alternatively, the poor solvent may be a solvent containing a base (such as an aqueous solution of sodium hydroxide).
[0070] In order to produce a membrane having a micro-nano composite network structure, the membrane may be produced using two or more polymers in step (1). That is, at least a first polymer and a second polymer may be dissolved in a solvent to prepare a polymer solution that is a membrane flow solution. The total concentration of the first polymer and the second polymer in the polymer solution may be 6 to 30% by weight, and preferably 10 to 25% by weight.
[0071] The types and weight ratios of the first polymer and the second polymer are as described above.
[0072] In this embodiment, the solvent may be a good solvent capable of dissolving the first polymer and the second polymer, examples of both solvents include, but are not limited to, one or more of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, N-methyl-2-pyrrolidone, dimethylsulfoxide, tetramethylsulfoxide, tetrahydrofuran, dioxane, acetonitrile, chloroform, etc.
[0073] In this embodiment, in step (2), the droplets of the atomization pretreatment may contain a poor solvent, particularly for the first polymer. The poor solvent may be a one-component solvent (such as water, ethanol and ethylene glycol). Alternatively, the poor solvent may be a mixed solvent containing water (such as a mixed solvent composed of water and a polar and aprotic solvent or other solvent). Alternatively, the poor solvent may be a solvent containing a salt, an acid or a base.
[0074] In this embodiment, in step (3), the coagulation bath may contain a poor solvent, particularly for the first polymer. The poor solvent may be a one-component solvent (such as water, ethanol and ethylene glycol). Alternatively, the poor solvent may be a mixed solvent containing water (such as a mixed solvent composed of water and a polar aprotic solvent or another solvent). Alternatively, the poor solvent may be a solvent containing a base (such as an aqueous solution of sodium hydroxide).
[0075] Due to the difference in solubility and wettability of the first and second polymers, the phase separation rate differs during non-solvent induced phase separation. This leads to the formation of a composite structure with a scaffold and nanoprojection structure. The nanoprojection structure improves the properties of the film, for example by increasing the roughness of the film, which improves the wettability.
[0076] In the present invention, the key technology for membrane production is the combination of atomization pretreatment and non-solvent induced phase separation (NIPS). For the first time, the present invention adds an atomization pretreatment step before the conventional non-solvent induced phase separation method.
[0077] The atomization pretreatment method of the present invention is significantly different from vapor-induced phase separation (VIPS) in the general sense, i.e., phase separation occurs under specific high humidity (or saturated humidity) conditions and does not involve an atomized droplet bath.
[0078] The formation of polymer membranes is a complex non-equilibrium process. The period during which phase separation occurs, the type of phase separation, and the degree to which phase separation occurs depend on the reaction rate factors of the phase separation process. The transfer and exchange of materials between the non-solvent and the solvent is one of the important factors that change the final membrane structure and properties. In the atomization pretreatment adopted in the present invention, the membrane casting solution can be uniformly partially phase-separated from the surface layer to the bottom layer by controlling the intrusion of non-solvent atomized droplets into the membrane casting solution. This provides the effect that the concentration gradient of the membrane casting solution is not observed in the thickness direction of the membrane in a short time (this point is similar to the membrane obtained by the conventional VIPS method). Then, the membrane structure is further completely phase-separated and completely solidified by the conventional non-solvent phase inversion method. In the manufacturing method of the present invention, the composition of the non-solvent in the membrane casting solution gradually changes. Therefore, the membrane structure produced by the atomization pretreatment process is almost uniform in the thickness direction, and therefore the surface layer structure and the bottom layer structure are almost the same. Thus, the cross-sectional structure of the resulting polymer membrane exhibits a polymer fiber skeleton and pores with a substantially uniform morphology across the thickness of the membrane.
[0079] The process according to the present invention is simple, efficient, low-cost, easy to industrialize, can be produced continuously, does not require high-pressure operation, is environmentally friendly, safe and energy-saving. The membrane can be produced from commodity polymers. Therefore, the raw materials are cheap and easily available. Moreover, the membrane can be produced easily on a large scale, is suitable for industrial applications and can be produced continuously.
[0080] In the manufacturing method of the present invention, the chemical composition and microstructure of the membrane surface can also be controlled by adjusting the parameters of the membrane casting solution preparation, the atomization pretreatment step and the NIPS process, thereby adjusting the wettability of the surface to achieve different performances such as separation or filtration.
[0081] [Use and Functional Materials] In a third aspect of the present invention, the present invention provides the use of the membrane according to the present invention for gas filtration, liquid filtration, oil-water separation, adsorption material, catalyst, drug sustained release material, anti-fouling coating, oil pumping or oil spill prevention, and other fields.
[0082] The membrane of the present invention has the same characteristics as the electrospun nanofiber membrane in terms of the skeletal structure. The membrane of the present invention is characterized by special wettability (superhydrophilicity, superoleophobicity in water), extremely low oil adhesion, and high specific surface area. The membrane of the present invention is environmentally friendly, has excellent stability, is resistant to contamination by oil, organic matter, biomass, bacteria, microorganisms, etc., is easy to wash and clean, and has excellent recyclability. The membrane of the present invention can replace part of the application market of the current electrospun nanofiber membrane. Examples of application markets include applications in liquid filtration, gas filtration, catalysis, adsorption, etc. in the environmental field, wound dressing materials in the bioengineering field, and battery separator materials in the energy field.
[0083] Compared with the membrane manufacturing technology by electrospinning, the present invention is characterized by the following points. First, the present invention can obtain the membrane of the present invention by simply adding atomization pretreatment before the non-solvent induced phase separation process currently commonly adopted in the industry. In the present invention, the manufacturing efficiency per minute reaches up to several meters, so that it is easy to apply to industry. In addition, the cross-sectional structure of the membrane of the present invention is similar to the cross-sectional structure of a nanofiber membrane. That is, the gaps formed by the pores of the through-hole structure in the membrane structure of the present invention are similar to the gaps between the overlapping fibers in the nanofiber membrane structure manufactured by electrospinning. At the same time, in the membrane formation process of the non-solvent phase inversion method, the polymer forms a polymer-rich phase during separation from the non-solvent and is firmly interconnected in three dimensions. Therefore, since the polymer fibers are connected to each other to form a strong three-dimensional mesh structure, it has excellent structural stability. Therefore, the pseudo-nanofiber structure membrane of the present invention is more suitable than conventional nanofiber membranes in liquid filtration that needs to withstand a certain degree of impact.
[0084] The membrane of the present invention (particularly, the membrane having a micron / submicron size recess structure on the surface or the membrane having a micro-nano composite network structure) can achieve the effect of oil-water separation without requiring a demulsification process to remove emulsified oil droplets. The membrane of the present invention quickly and efficiently separates mixtures of dichloroethane, n-hexane, petroleum ether, toluene, animal and vegetable oils, gasoline, diesel oil, heavy oil, crude oil, etc. with water. The membrane of the present invention can be used in fields such as oil-water separation, treatment of oil spills in the ocean, prevention of oil spills, anti-adhesion coating, and oil transportation. If a hydrophilic membrane is used, O / W emulsions can be filtered. If a hydrophobic membrane is used, W / O emulsions can be filtered.
[0085] The membrane having the micro-nano composite structure according to the present invention has a special micro-nano structure. Therefore, the three-phase contact line of solid-oil-water is discontinuous in water. This allows the membrane to separate oil while preventing oil adhesion, making it less susceptible to contamination and excellent in recyclability.
[0086] Correspondingly, in a fourth aspect of the present invention, the present invention provides a functional material comprising the membrane of the present invention. The functional material is used in the fields of gas filtration, liquid filtration, oil-water separation, adsorption material, catalyst, drug sustained release material, anti-adhesion coating, oil transport or oil spill prevention, etc. The functional material is particularly a separation membrane, preferably an oil-water separation membrane. Alternatively, the functional material is a filtration membrane, preferably a microfiltration membrane. [Brief description of the drawings]
[0087] [Figure 1] FIG. 1 is an image of the surface profile of the polymer film of Example 1. [Diagram 2] FIG. 2 is an image of the cross-sectional shape of the polymer membrane of Example 1. [Diagram 3] FIG. 3 is an image of the surface profile of the polymer film of Example 5. [Figure 4] FIG. 4 is an image of the cross-sectional profile of the polymer membrane of Example 5. [Diagram 5] FIG. 5 is an image of the surface profile of the polymer film of Example 6. [Figure 6] FIG. 6 is an image of the cross-sectional profile of the polymer membrane of Example 6. [Figure 7] FIG. 7 is an image of the surface profile of the polymer film of Comparative Example 1. [Figure 8] FIG. 8 is an image of the cross-sectional shape of the polymer film of Comparative Example 1. [Figure 9] FIG. 9 is a cross-sectional view of a prior art nanofibrous membrane. [Figure 10] Figure 10 is a photograph of the shape of a loofah sponge. [Figure 11] FIG. 11 is a scanning microscope photograph of the microfiltration membrane of Example 8. [Figure 12] FIG. 12 is a scanning electron micrograph (high magnification) of the microfiltration membrane of Example 8. EXAMPLES
[0088] The present invention will now be further described with reference to examples, but the scope of the present invention is not limited to these examples, and is as set forth in the appended claims.
[0089] [1.Measurement method] (1) Surface and cross-sectional shape of the membrane The surface and cross-sectional morphology of the films were observed using a high-resolution field emission scanning electron microscope (FESEM; S-4800, Hitachi, Japan). Samples for characterizing the cross-sectional morphology of the films were prepared by liquid nitrogen freeze brittle fracture method.
[0090] (2) Average pore size of the membrane The average pore size of the membrane was measured by gas permeation method. A microfiltration membrane pore size analyzer (PSDA-20) was used for the measurement. During the test, the sample was placed on the test table with the rough side facing up. Prior to the test, the sample was soaked in a test liquid (surface tension: 16 mN m -1 The membrane material was thoroughly wetted with 100% water. The test gas was nitrogen.
[0091] (3) Volume porosity of the membrane The porosity was measured by a gravimetric method and calculated according to the following formula. θ=1-V a / V g where θ is the volume porosity of the membrane. a is the true volume of polymer solids contained in a unit area of membrane sample. V g is the geometric volume occupied by the polymer layer of a unit area of the membrane sample.
[0092] (4) Size of the recesses and nanoprotrusions The size of the recesses was measured by measuring the opening diameter of the recesses on the film surface in the SEM photograph. The size of the nanoprotrusions was measured by measuring the diameter of the protrusion particles in the SEM photograph.
[0093] (5) Oil / water separation performance (oil / water flow rate, capture rate, oil / water flow rate after cleaning) [Preparation of oil-in-water emulsion] First, the emulsifier sodium dodecyl sulfate (SDS, concentration: 100 mg L -1 ) was dissolved in water. Then diesel oil was mixed. The volume ratio of diesel oil to water was 1:99. After mixing, the oil-water mixture was sonicated for 1 hour to prepare an emulsified milk-like emulsion. The diesel oil used was purchased from China Petroleum & Chemical Corporation (trade name: No. 0).
[0094] [Preparation of water-in-oil emulsion] Emulsifier Span 80 (concentration: 300 mg L -1 ) was added to the kerosene. Then, water was added. The volume of kerosene and water was adjusted to 99:1. After mixing, the oil-water mixture was sonicated for 1 hour to prepare an emulsified milk-like emulsion. The kerosene used was purchased from Aladdin Reagents (product number: K118401).
[0095] A cross-flow device was used to test the oil-water separation performance of the membrane. The test membrane was fixed in the cross-flow membrane cell with the front side facing up. The operating pressure was constant during the test. The separation flow rate of the membrane was calculated from the mass of filtrate collected in 1 minute and the effective separation area using the following formula. J = m / (A × t) In the formula, J is the separation flow rate of the membrane (in this case, the oil-water flow rate). m is the mass of liquid that passed during time t. A is the effective separation area of the membrane. The separation efficiency of the membrane was evaluated by investigating the total organic carbon content (TOC) in the filtrate. A total organic carbon analyzer (Multi NC3100) was used for the investigation. The calculation formula is as follows. E = (C0-C) / C0 x 100% where E is the separation efficiency (%) (in this case, the capture rate), C0 is the TOC value of the emulsion before separation, and C is the TOC value of the filtrate after separation.
[0096] The particle size of small oil or water droplets contained in the oil / water emulsion (O / W) or (W / O) prepared in the oil / water separation experiment was 0.3-3 μm. Most of the oil droplets were submicron scale (particle size was obtained from data analysis by a laser particle size analyzer (DLS)). A hydrophilic membrane was used to filter the O / W emulsion. A hydrophobic membrane was used to filter the W / O emulsion. The test pressure was adjusted to 1 kPa-0.2 MPa depending on the type of membrane. After one test, the test membrane was taken out and rinsed, and the oil / water flow rate after regeneration (oil / water flow rate after rinsing) was tested. In this way, the antifouling property and long-term usability were evaluated.
[0097] (6) Droplet diameter of atomized droplet bath The measurements were made using a laser particle size analyzer (Bettersize 2000S).
[0098] (7) Contact angle test Contact angle tests were performed at room temperature (approximately 25°C) using a contact angle measuring instrument (DSA100, Kruss, Germany). First, the sample film to be tested was fixed on a glass slide, and it was confirmed that the film surface was uniform. When testing the contact angle of liquids in air, the glass slide with the film fixed thereon was placed directly on the sample stage of the testing equipment. When testing the contact angle of oils in water, the film was wetted and then placed in a quartz water tank filled with water for testing. The oil used in the test was 1,2-dichloroethane. In this experiment, the volume of the test liquid used for the static contact angle test was 3 μL. The contact angle of the liquid droplet when it was in contact with the film surface for 3 seconds was taken as the contact angle value in this test.
[0099] 2. Materials and Equipment Used in the Examples and Comparative Examples (1) All chemical reagents used were commercially available products and, unless otherwise stated, were not subjected to any special purification treatment. Polyacrylonitrile (PAN): Purchased from Shaoxing Gimel Composite Materials Co., Ltd. (China). Product name: P60C. Nanosilica: purchased from Aladdin Reagents. Particle size: 30nm. Cellulose acetate (CA): purchased from InnoChem Science & Technology Co., Ltd. Polyvinylidene fluoride (PVDF): purchased from Solvay SA. Product name: 6010. Polystyrene (PS): purchased from Aladdin Reagents. Part number: P107090. Lithium chloride: purchased from InnoChem Science & Technology Co., Ltd. Polyvinylpyrrolidone: purchased from Macklin. K13-18. Average molecular weight: 10,000. Sulfonated Polyethersulfone: Purchased from Klamar. Product number: 091343. Polyethylene glycol: purchased from InnoChem Science & Technology Co., Ltd. Average molecular weight: 20,000. Polyethersulfone: purchased from BASF. Product name: E2010C6. Polyvinyl alcohol: purchased from Aladdin Reagents. Model: 1788. Pluronic F-127: Polyoxyethylene polyoxypropylene ether block copolymer. Purchased from Sigma Reagents. Non-woven fabric used: Purchased from Hirose, Japan. Model: 75AX. Polyester.
[0100] (2) Atomization device High pressure nozzle: SK508 (Huajue Technology Co., Ltd., Dongguan, China) ·Ultrasonic humidifier: HQ-JS130H (Haoqi, China) The droplet bath was deionized water. Data analysis with a laser particle size analyzer (DLS) showed that the droplet size of the atomized droplet bath used in the test was substantially between 0.3 and 10 μm.
[0101] Example 1 A certain mass of polyacrylonitrile (PAN) was weighed and dissolved in N-methylpyrrolidone (NMP). The solution was heated and stirred at 60°C until the polyacrylonitrile was fully dissolved. This prepared a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 200 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 30 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to cause complete phase separation. It was washed with water to obtain a membrane. In the membrane production process, the humidity was adjusted to a low humidity environmental condition of 20% to 35%. The average pore size of the membrane was 269 nm. The volume porosity of the membrane was 65.2%. This membrane can be used as a microfiltration membrane. The results of an oil-water separation experiment using the obtained membrane are shown in Table 1.
[0102] FIG. 1 shows the surface shape of the membrane obtained in Example 1 when observed by SEM. FIG. 2 shows the cross-sectional shape of the same membrane. The SEM images in FIG. 1 and FIG. 2 reveal the following. The polyacrylonitrile membrane of Example 1 had a loofah sponge-like structure. The surface and interior of the membrane formed a three-dimensional mesh-like pore structure that interpenetrated. The polymer fibers of the membrane were interwoven to form an interconnected three-dimensional fiber network. A clear recessed structure was observed on the surface of the obtained membrane, and the size of the recessed structure was 0.5 to 4 μm. The cross-sectional structure of the membrane contained polymer fibers and the same type of pores (mesh-like pores). In the fiber skeleton structure of the membrane, the average distance between two adjacent connection points in the thickness direction was smaller than the average distance between two adjacent connection points in the surface direction. As can be seen from FIG. 2, the polymer fibers of the obtained membrane had a hollow structure inside.
[0103] Example 2 A certain mass of polyacrylonitrile (PAN) and a certain mass of nanosilica were weighed. Nanosilica was thoroughly dispersed in N,N-dimethylformamide (DMF) (concentration: 2% by mass). Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF) (concentration: 6% by mass). The mixture was heated and stirred at 60°C until a uniform membrane casting solution was formed, and vacuum degassed. The prepared membrane casting solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 100 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 15 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to completely separate the phases. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a low humidity environmental condition of 30% to 38%. The average pore size of the obtained membrane was 314 nm. The volume porosity was 79.2%. This membrane can be used as a microfiltration membrane.
[0104] When observed with an SEM, the obtained membrane had a loofah sponge-like structure, and clear recessed structures were observed on the surface. The size of the recessed structures was 0.5 to 5 μm. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0105] Example 3 A certain mass of cellulose acetate (CA) was weighed and dissolved in acetone. The mixture was stirred to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a clean glass plate with a doctor blade to obtain a coating film with a thickness of 200 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 30 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to cause complete phase separation. The film was washed with water to obtain a membrane. In the membrane production process, the humidity was adjusted to a low humidity environmental condition of 15% to 30%. The average pore size of the obtained membrane was 106 nm. The volume porosity of the membrane was 83.1%. This membrane can be used as a microfiltration membrane.
[0106] When observed with an SEM, the membrane had a loofah sponge-like structure, with clear recesses on the surface. The size of the recesses was 1 to 4 μm. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0107] Example 4 A certain mass of polyacrylonitrile (PAN) was weighed and dissolved in DMF. The mixture was heated and stirred at 60°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 200 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 35 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of 1 mol / L sodium hydroxide aqueous solution to completely separate the phases. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a low humidity environmental condition of 20% to 35%. The average pore size of the obtained membrane was 435 nm. The volume porosity was 87.9%. This membrane can be used as a microfiltration membrane.
[0108] When observed with an SEM, the obtained membrane had a loofah sponge-like structure, and clear recessed structures were observed on the surface. The size of the recessed structures was 1 to 5 μm. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0109] Example 5 A certain mass of polyacrylonitrile (PAN) was weighed and dissolved in N-methylpyrrolidone (NMP). The mixture was heated to 60°C and stirred to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 40 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to cause complete phase separation. The film was washed with water to obtain a membrane. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 50% to 80%. The average pore diameter of the obtained membrane was 437 nm. The volume porosity was 71.3%. This membrane can be used as a microfiltration membrane.
[0110] Observation by SEM showed that the obtained membrane did not have a clear recessed structure on the surface. The surface shape of the obtained membrane is shown in FIG. 3, and the cross-sectional shape is shown in FIG. 4. The SEM images in FIG. 3 and FIG. 4 show the following. The polyacrylonitrile microfiltration membrane of Example 5 has a loofah sponge-like structure. The surface and interior of the membrane form a three-dimensional mesh-like pore structure that interpenetrates. The polymer fibers of the membrane are three-dimensionally interwoven and interconnected to form a three-dimensional fiber network (fiber skeleton structure). The cross-sectional structure of the membrane contained polymer fibers and the same type of pores (mesh-like pores). In the fiber skeleton structure of the membrane, the average distance between two adjacent connection points in the thickness direction was smaller than the average distance between two adjacent connection points in the surface direction.
[0111] The results of oil-water separation experiments using this membrane are shown in Table 1.
[0112] Example 6 A certain mass of polyvinylidene fluoride (PVDF) was weighed and dissolved in N-methylpyrrolidone (NMP). The mixture was heated and stirred at 70°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was vacuum degassed. The prepared raw material solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 40 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. The average pore diameter of the obtained membrane was 487 nm. The volume porosity was 71.0%. This membrane can be used as a microfiltration membrane. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 50% to 80%.
[0113] When observed by SEM, the obtained membrane did not have a clear recessed structure on the surface. The surface shape of the membrane obtained in Example 6 is shown in FIG. 5, and the cross-sectional shape is shown in FIG. 6. The SEM photographs in FIG. 5 and FIG. 6 reveal the following. The polyvinylidene fluoride microfiltration membrane of Example 6 had a loofah sponge-like structure. The surface and interior of the microfiltration membrane formed a three-dimensional mesh-like pore structure that interpenetrated. The polymer fibers of the microfiltration membrane were three-dimensionally interwoven and interconnected to form a three-dimensional fiber network (fiber skeleton structure). The cross-sectional structure of the microfiltration membrane contained polymer fibers and the same type of pores (mesh-like pores). In the fiber skeleton structure of the membrane, the average distance between two adjacent connection points in the thickness direction was smaller than the average distance between two adjacent connection points in the surface direction. The length of one polymer fiber was 1 to 4 μm, and the diameter of the fiber was 50 nm to 0.4 μm.
[0114] The results of oil-water separation experiments using this membrane are shown in Table 1.
[0115] Example 7 A certain mass of lithium chloride and a certain mass of polystyrene (PS) were weighed. Lithium chloride was thoroughly dispersed in N,N-dimethylformamide (DMF) (concentration: 0.5% by mass). Polystyrene (PS) was dissolved in N,N-dimethylformamide (DMF) (concentration: 6% by mass). The mixture was heated and stirred at 50°C until a uniform membrane casting solution was formed, and vacuum degassed. The prepared membrane casting solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. Next, the coating film was retained in an atomized droplet bath for 30 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to completely separate the phases. The film was washed with water to obtain a membrane. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 60% to 80%. The average pore diameter of the obtained membrane was 1217 nm. The volume porosity was 90.7%. This membrane can be used as a microfiltration membrane.
[0116] Observation with an SEM revealed that the obtained membrane had a loofah sponge-like structure, with no clear recessed structure observed on the surface. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0117] Comparative Example 1 A certain mass of polyacrylonitrile (PAN) was weighed and dissolved in NMP. The mixture was heated and stirred at 60°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. The fabric was then immersed in a coagulation bath of deionized water to completely invert the phase. The fabric was washed with water to obtain a membrane. The average pore size of this membrane was 35 nm. The volume porosity was 53.7%. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0118] The surface shape of the membrane of Comparative Example 1 is shown in FIG. 7, and the cross-sectional shape is shown in FIG. 8. From the SEM photographs of FIG. 7 and FIG. 8, the following can be seen. The surface of the membrane has a typical surface shape of a conventional flat ultrafiltration membrane. That is, the surface is substantially covered with a flat and uniform polymer layer, on which a small number of pores are distributed. In the cross section, the membrane had a sponge-like pore structure near the surface layer and a finger-like pore structure at the bottom. That is, the overall structure was not a loofah sponge-like structure.
[0119] Comparative Example 2 A certain mass of polyacrylonitrile (PAN) was weighed and dissolved in DMF. The mixture was heated and stirred at 60°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 200 μm. The film was then allowed to dwell for 40 seconds in a thermo-hygrostat at room temperature (25°C) and humidity of 100%. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The film was washed with water to obtain a membrane. The average pore size of the membrane was 40 nm. The volume porosity was 59.1%.
[0120] Observation with an SEM revealed that the obtained membrane did not have a loofah sponge-like structure. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0121] Comparative Example 3 A certain mass of cellulose acetate was weighed and dissolved in NMP. The mixture was heated and stirred at 60°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. The film was then immersed in a coagulation bath of deionized water to completely invert the phase. The film was washed with water to obtain a membrane. The average pore size of the membrane was 24 nm. The volume porosity was 52.8%.
[0122] Observation with SEM revealed that the obtained membrane did not have a loofah sponge-like structure. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0123] Comparative Example 4 A certain mass of polyvinylidene fluoride (PVDF) was weighed and dissolved in N-methylpyrrolidone (NMP). The mixture was heated and stirred at 70°C to prepare a raw material solution with a concentration of 8% by weight. The obtained raw material solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric with a doctor blade to obtain a coating film with a thickness of 150 μm. The fabric was then immersed in a coagulation bath of deionized water to cause complete phase separation. The fabric was washed with water to obtain a membrane. The average pore size of the obtained membrane was 48 nm. The volume porosity was 61.4%.
[0124] Observation with an SEM revealed that the obtained membrane did not have a loofah sponge-like structure. The results of an oil-water separation experiment using this membrane are shown in Table 1.
[0125] [Table 1]
[0126] As can be seen from the data in Table 1, the membranes having a loofah sponge-like structure produced in the examples of the present invention had superior oil-water separation properties compared to the membranes not having a loofah sponge-like structure produced in the comparative examples not included in the scope of the present invention. Specifically, the oil-water flow rate was equal to or higher, the capture rate was high, and the oil-water flow rate after washing was equal to or higher. In addition, the membranes had excellent anti-fouling properties and could be used for a long time.
[0127] Comparing the data of Comparative Example 1 and Example 5, and comparing the data of Comparative Example 4 and Example 6, it can be seen that the following: When the same membrane casting solution was used to directly prepare a membrane by non-solvent induced phase separation without atomization pretreatment, the oil-water separation function of the obtained membrane was very poor. Specifically, the capture rate and the oil-water flow rate after washing were both relatively low. In addition, no microfiltration membrane was obtained.
[0128] Example 8 8g of polyacrylonitrile and 8g of polyvinylpyrrolidone were dissolved in 84g of N,N-dimethylformamide (DMF). The mixture was heated and stirred at 50°C to obtain a homogeneous solution. The homogeneous solution was vacuum degassed. Next, the solution was coated on a nonwoven fabric to obtain a coating film with a thickness of 100 μm. Next, the coating film was allowed to stay in an atomized droplet bath for 30 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. Next, the film was immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 60% to 80%. The average pore size of the obtained membrane was 0.8 μm. The volume porosity was 80.3%. This membrane can be used as a microfiltration membrane.
[0129] The surface shape of the obtained film is shown in Figures 11 and 12. The SEM photographs in Figures 11 and 12 reveal the following: The film has a loofah sponge-like structure. The fibrous skeletal structure has projections of 50 to 250 nm distributed therein. The contact angle of the film with oil and water in air was 0°, and the contact angle with oil in water was 165°.
[0130] Example 9 12 g of sulfonated polyethersulfone and 1 g of polyethylene glycol were dissolved in 87 g of N-methyl-2-pyrrolidone (NMP). The mixture was heated and stirred at 60°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The obtained solution was then coated on a clean glass plate to obtain a coating film having a thickness of 300 μm. The coating film was then retained in an atomized droplet bath for 10 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The film was washed with water to obtain a membrane. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 65% to 85%. The average pore size of the obtained membrane was 0.3 μm. The volume porosity was 86.8%. This membrane can be used as a microfiltration membrane.
[0131] Observation with an SEM revealed that the obtained film had a loofah sponge-like structure, with protrusions of 40 to 300 nm distributed along the fibrous skeletal structure. The contact angles of the film with oil and water in air were both 0°, and the contact angle with oil in water was 158°.
[0132] Example 10 8g of polyethersulfone and 2g of polyvinyl alcohol were dissolved in 90g of dimethylsulfoxide (DMSO). The mixture was heated and stirred at 60°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The obtained solution was then coated on a nonwoven fabric to obtain a coating film having a thickness of 150μm. The coating film was then allowed to stay in a droplet bath of deionized water for 2 minutes. This droplet bath was atomized by a high-pressure gas flow sprayed from a high-pressure nozzle. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 70% to 90%. The average pore size of the obtained membrane was 4μm. The volume porosity was 83.8%. This membrane can be used as a microfiltration membrane.
[0133] Observation of the obtained film with SEM revealed that it had a loofah sponge-like structure, with 20-50 nm projections distributed along the fibrous skeletal structure. The contact angle of the film with oil and water in air was 0°, and the contact angle with oil in water was 152°.
[0134] Example 11 6g of polyethersulfone and 10g of Pluronic F-127 were dissolved in 84g of NMP solvent. The mixture was heated and stirred at 70°C to obtain a homogeneous solution. The homogeneous solution was vacuum degassed. The obtained solution was then coated on a nonwoven fabric to obtain a coating film having a thickness of 250μm. The coating film was then retained in an atomized droplet bath for 50 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 70% to 99%. The average pore size of the obtained membrane was 4.3μm. The volume porosity was 80.9%. This membrane can be used as a microfiltration membrane.
[0135] Observation with an SEM revealed that the obtained film had a loofah sponge-like structure, with 20-40 nm projections distributed along the fibrous skeletal structure. The contact angles of the film with oil and water in air were both 0°, and the contact angle with oil in water was 154°.
[0136] Example 12 6g of polyethersulfone and 18g of polyvinylpyrrolidone were dissolved in 76g of NMP. The mixture was heated and stirred at 70°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The obtained solution was then coated on a clean glass plate to obtain a coating film having a thickness of 100 μm. The coating film was then allowed to stay in an atomized droplet bath for 20 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 65% to 85%. The average pore size of the obtained membrane was 3 μm. The volume porosity was 91.3%. This membrane can be used as a microfiltration membrane.
[0137] Observation with an SEM revealed that the obtained film had a loofah sponge-like structure, with protrusions of 40 to 200 nm distributed along the fibrous skeletal structure. The contact angle of the film with oil and water in air was 0°, and the contact angle with oil in water was 155°.
[0138] Example 13 12 g of cellulose acetate and 10 g of polyethylene glycol were dissolved in 78 g of acetone. The mixture was heated and stirred at 70°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The obtained solution was then coated on a nonwoven fabric to obtain a coating film having a thickness of 100 μm. The coating film was then retained in an atomized droplet bath for 20 seconds. This atomized droplet bath was prepared by ultrasonically atomizing deionized water using an ultrasonic humidifier. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The membrane was obtained by washing with water. In the membrane production process, the humidity was adjusted to a relatively high humidity environmental condition of 60% to 80%. The average pore size of the obtained membrane was 1.6 μm. The volume porosity was 89.6%. This membrane can be used as a microfiltration membrane.
[0139] Observation with an SEM revealed that the obtained film had a loofah sponge-like structure, with protrusions of 50 to 300 nm distributed along the fibrous skeletal structure. The contact angles of the film with oil and water in air were both 0°, and the contact angle with oil in water was 158°.
[0140] Comparative Example 5 8g of polyacrylonitrile and 8g of PVP were dissolved in 84g of NMP. The mixture was heated and stirred at 60°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The prepared solution was uniformly blade-coated on a nonwoven fabric using a doctor blade to obtain a coating film having a thickness of 100 μm. The fabric was then immersed in a coagulation bath of deionized water to completely invert the phase. The fabric was washed with water to obtain a membrane. The average pore size of the obtained membrane was 53 nm. The volume porosity was 66.0%.
[0141] Observation with a SEM showed that the obtained film did not have a loofah sponge-like structure, and the film structure had no protrusions. The contact angles of the film with oil in air were 40°, with water in air, and with oil in water, respectively.
[0142] Comparative Example 6 12 g of sulfonated polyethersulfone and 1 g of polyethylene glycol were dissolved in 87 g of NMP. The mixture was heated and stirred at 60°C to obtain a homogeneous solution. The homogeneous solution was degassed under vacuum. The resulting solution was then coated on a clean glass plate to obtain a coating film having a thickness of 300 μm. The film was then allowed to dwell for 30 seconds in a thermo-hygrostat chamber at a temperature of 25°C and a humidity of 100%. The film was then immersed in a coagulation bath of deionized water to cause complete phase separation. The film was washed with water to obtain a membrane. The average pore size of the obtained membrane was 69 nm. The volume porosity was 58.2%.
[0143] Observation with SEM showed that the obtained membrane did not have a loofah sponge-like structure, and the membrane structure had no protrusions. The volume porosity of the membrane was 58%. The contact angles of the membrane with oil in air were 48°, with water in air, and with oil in water, respectively.
[0144] The oil-water separation flow rate and capture rate were measured for the membranes obtained in Examples 8 to 13 and Comparative Examples 5 and 6. The results are shown in Table 2.
[0145] [Table 2]
[0146] The data of Comparative Example 5 and Example 8 are compared to show the following. That is, when the same membrane casting solution is used to directly prepare a membrane by non-solvent induced phase separation without atomization pretreatment, the oil-water separation function of the obtained membrane is very poor, and a microfiltration membrane cannot be obtained. The data of Comparative Example 6 and Example 9 are compared to show the following. That is, when gas-phase induced phase separation under high humidity is first performed, and then non-solvent phase inversion is performed, the oil-water separation function of the obtained membrane is very poor, and a microfiltration membrane cannot be obtained. The data of Example 8 and Example 1 are compared to show the following. That is, compared with the microfiltration membrane prepared by the manufacturing method of the present invention using a mixture of two types of polymers, the microfiltration membrane prepared by the manufacturing method of the present invention using a mixture of two types of polymers has a micro-nano composite structure and has excellent oil-water separation function.
[0147] 〔summary〕 The present invention includes the following aspects. <1> a fibrous framework formed by three-dimensionally interwoven and interconnected polymer fibers; a mesh-like pore structure that is distributed in the fiber skeleton structure and that three-dimensionally interpenetrates with one another; A polymer-based membrane having a loofah sponge-like structure, comprising: The polymer is an organic polymer, the fibrous skeletal structure being integrally formed from the polymer; The volume porosity of the film is 50% to 95%. film. <2> The volume porosity of the film is 65% to 95%; Preferably, it is 80% to 95%. Characterized in that <1> The membrane according to claim 1. <3> The average pore size of the membrane is 0.01 to 5 μm, Preferably, it is 0.1 to 3 μm. Characterized in that <1> or <2> The membrane according to claim 1. <4> In the above fiber skeletal structure, the average distance between two adjacent connection points in the thickness direction is smaller than the average distance between two adjacent connection points in the surface direction. <1> ~ <3> 2. The membrane according to claim 1 . <5> The cross section of the membrane has a network of pores distributed in the thickness direction of the membrane, substantially free of other types of pores (such as sponge-like pores and / or finger-like pores); Characterized in that <1> ~ <4> 13. The membrane according to any one of claims 1 to 12. <6> Characterized in that it satisfies the following (i) and / or (ii): <1> ~ <5> A membrane according to any one of the following: (i) in the fibrous framework of the membrane, the cross-sectional diameter of one polymer fiber between two junctions is 2 μm or less, and preferably the cross-sectional diameter varies irregularly; (ii) In the fibrous framework of the membrane, the length of one polymer fiber between two junctions is less than 10 μm. <7> The polymer fiber is characterized in that it has a hollow structure therein. <1> ~ <6> 2. The membrane according to claim 1 . <8> The polymer is selected from polymers suitable for membrane formation by a non-solvent induced phase separation method; Preferably, it is selected from hydrophilic or lipophilic polymers, More preferably, the polymer is at least one selected from the group consisting of polyvinylidene fluoride, polysulfone, polyethersulfone, polyacrylonitrile, polyacrylic acid, polyamide, chitosan, polyimide, modified cellulose (e.g., cellulose acetate), polystyrene, polyolefin, polyester, polychlorotrifluoroethylene, polyvinyl chloride, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, modified starch, polyvinylamine hydrochloride, polyethyleneimine, poly-N-isopropylacrylamide, and modified polymers thereof (e.g., polyvinylidene fluoride modified by grafting with acrylic acid, sulfonated polysulfone, maleic anhydride grafted polysulfone, sulfonated polyethersulfone, and acrylic acid grafted polyacrylonitrile). Characterized in that <1> ~ <7> 2. The membrane according to claim 1 . <9> The surface of the film has a micro / submicron recess structure, loofah sponge-like structures are distributed on, around or between the recessed structures; Preferably, the size of the recessed structure measured by SEM is 0.5 to 10 μm. Characterized in that <1> ~ <8> 2. The membrane according to claim 1 . <10> The fiber skeletal structure has nanoscale protrusions distributed thereon, the protrusions are integrally formed with the skeleton; Preferably, the protrusions are particulate, Preferably, the size of the protrusions measured by SEM is 20 to 400 nm, Preferably, the average pore size of the membrane is 0.1 to 5 μm. Characterized in that <1> ~ <9> 2. The membrane according to claim 1 . <11> The membrane comprises a mixture of two or more polymers; Preferably, the two or more polymers are soluble or miscible in the same good solvent, More preferably, (i) the first polymer is one or more selected from the group consisting of polyvinyl chloride, polysulfone, polyethersulfone, sulfonated polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, acrylonitrile-styrene copolymer, and modified polymers thereof, and (ii) the second polymer is one or more selected from the group consisting of chitosan, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyoxyethylene-polyoxypropylene ether block copolymer, More preferably, the weight ratio of the first polymer to the second polymer is 1:(0.01 to 5), preferably 1:(0.1 to 3). Characterized in that <10> The membrane according to claim 1. <12> The membrane has a micro-nano composite network structure made of two or more hydrophilic polymers; The hydrophilic polymer is superhydrophilic and superoleophilic in air; Preferably, the hydrophilic polymer has a contact angle with water and oil in air of less than 10°, more preferably less than 5°; Preferably, the hydrophilic polymer has a contact angle with oil in water of more than 135°, preferably more than 150°. Characterized in that <10> or <11> The membrane according to claim 1. <13> The membrane has a micro-nano composite network structure made of two or more hydrophobic polymers; The hydrophobic polymer is superhydrophobic in air, Preferably, the hydrophobic polymer has a contact angle with water in air of greater than 130°, more preferably greater than 150°; Preferably, the hydrophobic polymer has a contact angle with oil in water of less than 10°, preferably less than 5°. Characterized in that <10> or <11> The membrane according to claim 1. <14> Characterized in that it satisfies the following (i) and / or (ii): <1> ~ <13> A membrane according to any one of the following: (i) further comprising an additive, preferably comprising inorganic nanoparticles (such as MnO2, SiO2 and ZnO); Contains inorganic salt porogens (such as LiCl, ZnCl2, MgCl2 and LiBr). <15> The membrane is characterized in that it is present on a support layer (e.g., a fabric, preferably a nonwoven fabric), <1> ~ <14> 2. The membrane according to any one of claims 1 to 11. <16> The membrane is characterized in that it is produced by a combination of a non-solvent induced phase separation method and an atomization pretreatment; <1> ~ <15> 2. The membrane according to any one of claims 1 to 11. <17> <1> ~ <15> A method for producing the membrane according to any one of the above, subjecting a membrane casting solution containing a polymer to a combination of a non-solvent induced phase separation process and an atomization pretreatment to produce said membrane; Manufacturing method. <18> The method comprises the following steps (1) to (3): <17> The manufacturing method described in (1) A step of dissolving a polymer in a solvent to prepare a polymer solution which is a membrane casting solution; (2) applying the polymer solution in a film form (e.g., by blade coating) followed by pre-atomization by residence in a bath of atomized droplets; (3) A step of immersing the product obtained in step (2) in a coagulation bath to obtain the membrane. <19> In the above step (1), the concentration of the polymer solution is 5 to 30% by weight, preferably 5 to 25% by weight, and more preferably 6 to 20% by weight. Preferably, the solvent is selected from good solvents for the polymer; Preferably, the solvent is one or more selected from the group consisting of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide, dimethylsulfoxide, tetrahydrofuran, dioxane, acetonitrile, acetone, chloroform, toluene, benzene, hexane, octane, and tetramethylsulfoxide. Characterized in that <18> The manufacturing method described in <20> In the step (2), the polymer solution is uniformly coated on a support layer or a substrate to form a film; Preferably, the film to be applied is 50 to 500 μm, preferably 75 to 300 μm. Characterized in that <18> or <19> The manufacturing method described in <21> The step (2) is characterized in that it satisfies one or more of the following (i) to (iii): <18> ~ <20> A method for producing the same according to any one of the preceding claims, (i) the size of the droplets in the droplet bath is 1 to 50 μm, preferably 5 to 18 μm; (ii) the time for the pre-atomization treatment is from 1 second to 20 minutes, preferably from 5 seconds to 3 minutes, and more preferably from 5 to 60 seconds; (iii) the droplets contain a poor solvent for the polymer, preferably the poor solvent is selected from the group consisting of water, ethanol, ethylene glycol, mixed solvents containing water, and solutions containing a salt, an acid, or a base. <22> The environmental humidity in the above step (2) is a relatively high humidity condition of 40% or more, Preferably, the temperature is room temperature. Characterized in that <18> ~ <21> The method for producing a product according to any one of claims 1 to 5. <23> The environmental humidity in the above step (2) is a relatively low humidity condition of less than 40%, Preferably, the temperature is room temperature. Characterized in that <18> ~ <21> 13. The method for producing a semiconductor device according to any one of the preceding claims. <24> In the step (3), the coagulation bath contains a poor solvent for the polymer, The anti-solvent is the same as or different from the solvent contained in the droplets of the droplet bath; Characterized in that <18> ~ <23> 13. The method for producing a semiconductor device according to any one of the preceding claims. <25> The membrane contains a mixture of two or more types of polymers and is characterized in that it satisfies one or more of the following (i) to (iii): <18> ~ <24> A method for producing the same according to any one of the preceding claims, (i) in the above step (1), at least a first polymer and a second polymer are dissolved in a good solvent for the first polymer and the second polymer to prepare a polymer solution, and preferably, the total concentration of the polymers in the polymer solution is 6 to 30% by weight, more preferably 10 to 25% by weight; (ii) in step (2), the droplets in the droplet bath are a poor solvent for the first polymer; (iii) In step (3), the coagulation bath contains a poor solvent for the first polymer. <26> In the above step (2), the above polymer solution is uniformly applied onto a support layer (e.g., a cloth, preferably a nonwoven fabric); The above coating method is a roll-to-roll continuous method, Characterized in that <18> ~ <25> 13. The method for producing a semiconductor device according to any one of the preceding claims. <27> For the fields of gas filtration, liquid filtration, oil-water separation, adsorption materials, catalysts, pharmaceutical sustained release materials, anti-adhesion coatings, oil conveying or oil spill prevention, <1> ~ <16> or <17> ~ <26> Use of a membrane produced by any one of the production methods described above. <28> <1> ~ <16> or <17> ~ <26> A functional material comprising a film produced by any one of the production methods described in The above functional materials are used in the fields of gas filtration, liquid filtration, oil-water separation, adsorption materials, catalysts, pharmaceutical sustained release materials, anti-adhesion coatings, oil transport or oil spill prevention, A functional material which is either (i) or (ii) below: (i) Preferably, it is a separation membrane, more preferably an oil-water separation membrane. (ii) A filtration membrane, more preferably a microfiltration membrane.
Claims
1. a fibrous framework formed by three-dimensionally interwoven and interconnected polymer fibers; a mesh-like pore structure that is distributed in the fiber skeleton structure and that three-dimensionally interpenetrates with one another; A membrane based on an organic polymer having a loofah sponge-like structure, comprising: the fibrous skeletal structure being integrally formed from the polymer; The volume porosity of the membrane is 65 to 95%; the membrane is a microfiltration membrane having an average pore size of 0.1 to 10 μm as measured by gas permeation methods using a pore size analyzer; the polymer is at least one selected from the group consisting of polyvinylidene fluoride, polysulfone, polyethersulfone, polyacrylonitrile, polyacrylic acid, polylactic acid, polyamide, chitosan, polyimide, cellulose acetate, polystyrene, polyolefin, polyester, polychlorotrifluoroethylene, polyvinyl chloride, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, polyvinylamine hydrochloride, polyethyleneimine, poly-N-isopropylacrylamide, and modified polymers thereof; The modified polymer is selected from polyvinylidene fluoride modified by acrylic acid grafting, sulfonated polysulfone, maleic anhydride grafted polysulfone, sulfonated polyethersulfone and acrylic acid grafted polyacrylonitrile; film.
2. The volume porosity of the film is 80 to 95%. The membrane according to claim 1 .
3. The membrane has an average pore size of 0.1 to 5 μm as measured by a gas permeation method using a pore size analyzer; 3. A membrane according to claim 1 or 2, characterized in that
4. In the above fiber skeletal structure, the average distance between two adjacent connection points in the thickness direction is smaller than the average distance between two adjacent connection points in the surface direction. A membrane according to any one of claims 1 to 3.
5. In the fibrous framework of the membrane, the cross-sectional diameter of one polymer fiber varies randomly; A membrane according to any one of claims 1 to 4.
6. The polymer fiber has a hollow structure therein. A membrane according to any one of claims 1 to 5.
7. The surface of the film has a recessed structure, loofah sponge-like structures are distributed on, around or between the recessed structures; The size of the recessed structure measured by a scanning electron microscope is 0.5 to 10 μm, The size of the recessed structure is characterized by the diameter of the opening of the recessed portion on the film surface in a SEM photograph. The membrane according to any one of claims 1 to 6.
8. The fiber skeletal structure has nanoscale protrusions distributed thereon, The protrusions are integrally formed with the fiber skeletal structure. A membrane according to any one of claims 1 to 7.
9. The size of the protrusions, as measured by a scanning electron microscope, is 20 to 400 nm; The size of the protrusions is the diameter of the protrusions in the SEM photograph. The membrane according to claim 8 .
10. The average pore size of the membrane, as measured by gas permeation method using a pore size analyzer, is 0.1 to 5 μm.
10. A membrane according to claim 8 or 9.
11. The membrane comprises a mixture of two or more polymers. A membrane according to any one of claims 8 to 10, characterized in that
12. The two or more polymers are soluble or miscible in the same good solvent. The membrane according to claim 11 .
13. the first polymer is at least one selected from the group consisting of polyvinyl chloride, polysulfone, polyethersulfone, sulfonated polyethersulfone, polyacrylonitrile, cellulose acetate, polyvinylidene fluoride, polyimide, acrylonitrile-styrene copolymer, and modified polymers thereof; The second polymer is at least one selected from the group consisting of chitosan, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyoxyethylene-polyoxypropylene ether block copolymers; The membrane according to claim 11 .
14. The weight ratio of the first polymer to the second polymer is 1:(0.01 to 5); 14. The membrane according to claim 13.
15. The membrane has a micro-nano composite network structure composed of two or more types of hydrophilic polymers, The membrane is It is superhydrophilic and superoleophilic in air, The contact angles with water and oil in air are both less than 10°. A membrane according to any one of claims 8 to 14, characterized in that
16. The hydrophilic polymer has a contact angle with oil in water of more than 135°.
16. The membrane according to claim 15.
17. The membrane has a micro-nano composite network structure made of two or more hydrophobic polymers; The membrane is It is superhydrophobic in air, The contact angle with water in air is greater than 130°. A membrane according to any one of claims 8 to 16, characterized in that
18. The hydrophobic polymer has a contact angle with oil in water of less than 10°.
18. The membrane according to claim 17.
19. The film further comprises an additive selected from inorganic nanoparticles and inorganic salt porogens. A membrane according to any one of claims 1 to 18.
20. The inorganic nanoparticles are MnO 2 , SiO 2 and ZnO; The inorganic salt porogens are LiCl, ZnCl 2 , MgCl 2 and LiBr; 20. The membrane according to claim 19.
21. The membrane is on a support layer. A membrane according to any one of claims 1 to 20.
22. The support layer is a fabric.
22. The membrane according to claim 21 .
23. The support layer is a nonwoven fabric.
22. The membrane according to claim 21 .
24. A method for producing the membrane according to any one of claims 1 to 23, comprising the steps of: subjecting a membrane casting solution containing a polymer to a combination of a non-solvent induced phase separation process and an atomization pretreatment to produce said membrane; A production method comprising the following steps (1) to (3): (1) A step of dissolving a polymer in a solvent to prepare a polymer solution which is a membrane casting solution; (2) A step of applying the polymer solution in a film form and then performing a pretreatment by atomization, The pre-atomization treatment is performed by allowing the mixture to dwell in a bath of atomized droplets; (3) A step of immersing the product obtained in step (2) in a coagulation bath to obtain the membrane.
25. In the step (2), the polymer solution is applied in the form of a film by blade coating.
25. The method of claim 24.
26. In the step (1), the concentration of the polymer solution is 5 to 30% by weight. The method according to claim 24 or 25,
27. In the above step (1), the solvent is is selected from good solvents for the polymer, one or more selected from the group consisting of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide, dimethylsulfoxide, tetrahydrofuran, dioxane, acetonitrile, acetone, chloroform, toluene, benzene, hexane, octane, and tetramethylsulfoxide; The method according to any one of claims 24 to 26.
28. In the step (2), the polymer solution is uniformly coated on a support layer or a substrate to form a film. The method according to any one of claims 24 to 27.
29. In the step (2), the film thickness of the polymer solution to be applied is 50 to 500 μm.
29. The method of claim 28.
30. The method according to any one of claims 24 to 29, characterized in that the step (2) satisfies one or more of the following (i) to (iii): (i) the size of the droplets of the atomized droplet bath is 1 to 50 μm; (ii) the time of the pre-atomization treatment is from 1 second to 20 minutes; (iii) the droplets contain a poor solvent for the polymer, the poor solvent being selected from the group consisting of water, ethanol, ethylene glycol, a mixed solvent containing water, and a solution containing a salt, an acid, or a base.
31. The environmental humidity in the above step (2) is 40% or more. The temperature is room temperature. The method according to any one of claims 24 to 30.
32. The environmental humidity in the above step (2) is less than 40%. The temperature is room temperature. The method according to any one of claims 24 to 30.
33. In the step (3), the coagulation bath contains a poor solvent for the polymer, The anti-solvent is the same as the solvent contained in the droplets of the atomized droplet bath; The method according to any one of claims 24 to 32.
34. The method according to any one of claims 24 to 33, characterized in that the membrane contains a mixture of two or more types of polymers and satisfies one or more of the following (i) to (iii): (i) in the step (1), at least a first polymer and a second polymer are dissolved in a good solvent for the first polymer and the second polymer to prepare a polymer solution, and the total concentration of the polymers in the polymer solution is 6 to 30% by weight; (ii) in the step (2), the droplets in the atomized droplet bath are a poor solvent for the first polymer; (iii) In the above step (3), the coagulation bath contains a poor solvent for the first polymer.
35. In the step (2), the polymer solution is uniformly applied onto a support layer; The coating method is a roll-to-roll continuous method. The method according to any one of claims 24 to 34.
36. The support layer is a fabric.
36. The method of claim 35.
37. The support layer is a nonwoven fabric.
36. The method of claim 35.
38. Use of the membrane according to any one of claims 1 to 23 for the fields of gas filtration, liquid filtration, oil-water separation, adsorption materials, catalysts, pharmaceutical sustained release materials, anti-fouling coatings, oil pumping or oil spill prevention.
39. A functional material comprising the film according to any one of claims 1 to 23, The above functional materials are used in the fields of gas filtration, liquid filtration, oil-water separation, adsorption materials, catalysts, pharmaceutical sustained release materials, anti-adhesion coatings, oil transport or oil spill prevention; Functional materials.
40. Oil-water separation membrane, The functional material according to claim 39 .